Observing Legislative Processes: Implementation of the CRPD - Lamplmayr, Alexander (Innsbrucker Beiträge zur Rechtstatsachenforschung, 2016)
The series "Innsbrucker Beiträge zur Rechtstatsachenforschung" ("Innsbruck' contributions to empirical legal studies") aims at analysing the interconnections of law in the books and law in action with a special focus on the functioning of law. Volume 8 presents the results of the research project "Observing legislative processes: Implementation of the CRPD" which was funded by the Austrian Science Fund (FWF). The main focus of the project was the evaluation of the involvement of persons with disabilities in the processes of implementing the CRPD into domestic law and their involvement in the monitoring of these implementation processes within Austria, Germany, Australia and New Zealand. - Die Reihe "Innsbrucker Beiträge zur Rechtstatsachenforschung" verfolgt das Ziel, die gesellschaftlichen Grundlagen des Rechts und seine tatsächliche Anwendung darzustellen und zu analysieren. Mit Band 8 wird eine Zusammenschau der Ergebnisse des vom FWF - Der Wissenschaftsfonds geförderten Forschungsprojekts "Observing legislative processes: Implementation of the CRPD" geboten. In dem Projekt wurde analysiert, wie Menschen mit Behinderungen in nationale Umsetzungs- und Monitoringprozesse der UN-Behindertenrechtskonvention in Österreich, Deutschland, Australien und Neuseeland eingebunden werden.